POTENSI AGROFORESTRI KOPI UNTUK WISATA ALAM DI KESATUAN PENGELOLAAN HUTAN LINDUNG BATUTEGI - Nurrahman, Muhammad Irfan; Darmawan, Arief; Wulandari, Christine; Kaskoyo, Hari; Febryano, Indra Gumay; Novriyanti, Novriyanti; Iswandaru, Dian; Herwanti, Susni; Fitriana, Yulia Rahma; Safe’i, Rahmat (Universitas Pattimura, 2023)
Coffee agroforestry in protected forest areas has the potential to be operated as a nature tourism destination. The purpose of this study was to analyze the feasibility of coffee agroforestry in the KPHL Batutegi area as a nature tourism area. Data collection was conducted by field observation and interviews using questionnaires. Data analysis was carried out using a modification of the Directorate General of Nature Tourism Object Operations (ADO-ODTWA) guidelines in 2003. The results showed that the potential of coffee agroforestry in KPHL Batutegi bordering Penantian Village and Sinar Banten Village has a medium potential value index. This means that the coffee agroforestry area in KPHL Batutegi has criteria that are not yet feasible to develop, because the element of accessibility (infrastructure), especially in the type of road taken with poor road conditions, makes it difficult to access the coffee agroforestry area. Tourism objects in the medium classification can be developed because a lot of planning is needed in structuring a good area in the future.